SWOT Analysis in a Healthy Bureaucracy for Advanced Indonesia - Nasuhi, M; Saputra, Didin Hadi; Mufidah, Mufidah (PINISI Discretion Review, 2022)
Bureaucracy in Indonesia is currently a very important issue in the era of downsizing and implementing a sound bureaucratic reform system. The purpose of writing this article is to provide constructive ideas and suggestions and build objective thinking. The method used in this writing or research is through the SWOT analysis method. The findings that we get in writing this paper or article are an effort that has been made by the government in an effort to simplify and improve the bureaucratic system in Indonesia through an analysis of the strengths and weaknesses of public services, as well as turning these strengths and weaknesses into opportunities and minimizing threats. The value of this study shows that the recruitment of civil servants by the government has a significant impact on improving the quality of services that have been produced through a long-term process to produce future leaders who are accountable, transparent, and able to demonstrate the art of leading from an early age and become a communication bridge between the government and the community.